A Physically Based Model for Non‐Point Source Pollutant Wash‐Off Process Over Impervious Surfaces - Xue Tong; Qiuhua Liang; Graham Sander; Gang Wang; Xijun Lai (Water Resources Research)
Abstract Physically based urban wash‐off modeling presents a promising approach for investigating the dynamics of road‐deposited sediments (RDS) and the associated pollutants during rainfall events. This paper proposes a novel physically based model to predict urban wash‐off process over impervious surfaces, where raindrop‐induced detachment, flow‐driven detachment and deposition are computed separately. This is achieved by modifying the Hairsine‐Rose (HR) model to account for sediment trapping due to road roughness, and incorporating multi‐sized particles to capture shielding effects during detachment and particle‐size selection during deposition across varying particle size distributions (PSDs). The model is validated through laboratory experiments, including single‐size particle simulations under varying rainfall conditions and particle sizes, and multi‐size particle simulations with different PSDs. Numerical experiments are conducted to systematically examine the relationships between model parameters and influencing factors (i.e., rainfall intensity and particle size). The results enhance parameter interpretation and simplify the model. Model predictions show strong agreement with experimental measurements, demonstrating that model parameters correlate with respective influencing factors and remain physically interpretable. By incorporating multi‐sized particles to reflect the PSD, the model effectively captures the particle‐size selection phenomenon during detachment and deposition. This study provides new insights into RDS wash‐off process modeling.